2013
DOI: 10.1371/journal.pone.0066153
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Staphylococcus aureus from Patients with Surgical Site Infections at Mulago Hospital in Kampala, Uganda

Abstract: BackgroundThe prevalence of Methicillin resistant Staphylococcus aureus (MRSA) is progressively increasing globally with significant regional variation. Understanding the Staphylococcus aureus lineages is crucial in controlling nosocomial infections. Recent studies on S. aureus in Uganda have revealed an escalating burden of MRSA. However, the S. aureus genotypes circulating among patients are not known. Here, we report S. aureus lineages circulating in patients with surgical site infections (SSI) at Mulago Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
72
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(91 citation statements)
references
References 32 publications
16
72
3
Order By: Relevance
“…Because SCC mec type IV and V are known to be small and highly mobile elements, their dissemination in a community population may be most commonly by transfers of strains from carriers to other individuals or from MRSA strains to Methicillin Sensitive Staphylococcus aureus (MSSA strains), or even from coagulase-negative staphylococci strain to an MSSA strain [41]. However, a recent study on patients with surgical site infections (SSI) at the National Referral hospital in Mulago, Kampala, showed that SCC mec type V was the most predominant type [22], suggesting the presence of mixed CA-MRSA and HA-MRSA genotypes in hospital settings in Uganda.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because SCC mec type IV and V are known to be small and highly mobile elements, their dissemination in a community population may be most commonly by transfers of strains from carriers to other individuals or from MRSA strains to Methicillin Sensitive Staphylococcus aureus (MSSA strains), or even from coagulase-negative staphylococci strain to an MSSA strain [41]. However, a recent study on patients with surgical site infections (SSI) at the National Referral hospital in Mulago, Kampala, showed that SCC mec type V was the most predominant type [22], suggesting the presence of mixed CA-MRSA and HA-MRSA genotypes in hospital settings in Uganda.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of MRSA in five African cities, only one strain of this type was isolated from Antananarivo, and none from Cassablanca (Moroco), Niamey (Niger), Dakar (Senegal) and Yaoundé (Cameroon). While SCC mec type V strains have been isolated from hospital settings in Uganda, none were Spa type t318 [22]. However, Spa type t645, the second most frequent type in our collection (20.6%), also common in Western Europe and the Middle East (http://spaserver.ridom.de), was found to be the most frequent type isolated from SSI at Mulago National referral hospital [22], supporting the notion that there is a changing epidemiology reflected by community associated SCC mec genotypes being now more associated with hospital infections as observed elsewhere [23, 45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of the mecA gene encoding penicillinbinding protein 2a (PBP2a) of S. aureus isolates were confirmed using a PCR assay, as previously described by Seni J. et al [14]. Briefly, amplification of the mecA gene was performed using the specific primers (forward primer 5'-GTAGAAATGACTGAACGTCCGATAA-3'…”
Section: Molecular Assay For Detection Of Meca Genementioning
confidence: 99%